INSIGHTS ON DRUG TARGETING OF TOXOPLASMA GONDII HOST INVASION PROTEINS: A REVIEW - Thirumudi, Indhuja; Umashankar Vetrivel; B, Mahalakshmi; Therese K, Lily; Hn, Madhavan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Toxoplasma gondii is an obligate intracellular parasite that infects homoeothermic animals. It is also the major cause of retinochoroiditis in humans. Drugs targeting T. gondii proteins involved in the establishment of host-pathogen interactions is well documented to be an efficient way to combat the infections. Basically, parasitic invasion of T. gondii occurs by the sequential secretion of apical membrane antigen 1 and rhoptry neck proteins on the parasite and host cell surfaces, respectively. These proteins operate synergistically and form the moving junction (MJ) complex, thereby, enabling attachment and penetration of the parasite into the host cell. Better understanding of molecular interactions of these proteins is essential to develop highly efficient therapeutic modalities. Hence, by this review it is intended to update the current status of rhoptry and other MJ complex proteins as ideal candidates for targeting T. gondii. Keywords: Toxoplasma gondii, Rhoptry proteins, Moving junction complex, Toxoplasmosis.